A revised evolutionary history of Poales: origins and diversification. (4th April 2014) - Bouchenak‐Khelladi, Yanis; Muasya, A. Muthama; Linder, H. Peter
<x xml:space="preserve">Abstract</x> Poales represents more than one‐third of all monocotyledons (c. 20 000 species in 16 families) and constitutes a microcosm of the angiosperms. The extreme variation in species richness among the families of Poales is still not understood: Poaceae includes ∼10 000 species, whereas six families have fewer than ten species. Here, using the largest phylogenetic analysis of Poales to date, molecular dating, ancestral reconstructions and diversification analyses, we develop a macro‐evolutionary and macro‐ecological approach to seek correlates for changing diversification patterns. We show that the poalean families diverged in the Late Cretaceous, a time of high levels of CO2 and high rainfall. Our habitat reconstructions indicate that Poales inhabited open and dry habitats in this environment. We also demonstrate that lineages with CO2‐concentrating mechanisms inhabiting dry and open environments exhibited higher diversification rates than C3, shade and wet lineages. CO2‐concentrating mechanisms counteract the effects of low atmospheric CO2 and reduce phototranspiration. It is believed that the parallel evolution of C4 and CAM (Crassulacean acid metabolism) photosynthesis in Poaceae, Cyperaceae and Bromeliaceae is an adaptation to changes in atmospheric CO2 concentrations. Combinations of extrinsic and intrinsic factors might have played a role in shifts in diversification rates and may explain the variation in species richness in Poales. © 2014 The Linnean Society of London, Botanical Journal of the Linnean Society, 2014, 175, 4–16.